Effect of brainstorming on students' achievement in junior secondary schools mathematics: an effort in making schools effective (2008)
One of the measures of the school effectiveness is the students' academic achievements (in this study Mathematics is used). The poor achievement of students in Mathematics both at school and public examinations has been aconcern to Mathematics educators. The failure rate may be due to how the subject is taught. This study, therefore, examines the effect of brainstorming on students' learning outcomes in Junior Secondary School Mathematics. The study adopted a quasi experimental design with pre test- post test control group. Two instruments (Mathematics Achievement Test and Numerical Ability Test) were used to collect data. The result shows that students exposed to brainstorming strategy out performed those in the control group. Students with high ability exposed to brainstorming are better achievers in Mathematics than the low ability students. The implication of the study is discussed.